Social network of sexual and gender minorities: possibilities of support in health care - Santana , Ane Martins da Silva; Souza, Maria Helena do Nascimento; Gomes, Margareth Cristina de Almeida; Rodrigues, Andreza Pereira; Torres, Juliana Lustosa; Pinho, Adriana de Araújo (Acta Scientiarum. Health Sciences, 2023)
The study aimed to characterize the Social Network of sexual and gender minorities and to analyze the type of social support received for health care. This was a descriptive qualitative study. The methodological theoretical framework of Social Network proposed by Lia Sanicola was used. Semi-structured interviews were analyzed based on the Content Analysis technique proposed by Bardin. The study was carried out in 2019 at a family health unit in the city of Rio de Janeiro. Results showed that the social network of the interviewees was marked by a strong relationship with friends and colleagues, while in the relationship with family members there was a greater fragility in the bonds due to the lack of knowledge or non-acceptance of these members in relation to the sexuality of the interviewees. In addition to the fragility of the family relationship, there was a difficulty and discontinuity in access to health, due to the lack of bonds stimulated by prejudice and discrimination in health services. Social networks were characterized by the bond with friends and colleagues who offered emotional support. In the context of the family and the health care network, social relationships were permeated with weaknesses and lack of support. Knowledge of the network and the type of social support received by people who are part of sexual and gender minorities makes it possible to broaden the health professional’s view of comprehensive care for this population and consequently improve the quality of care provided.